ARTIFICIAL INTELLIGENCE IN EDUCATION: ENABLING PERSONALIZED LEARNING AND ENHANCED NETWORKING - Ravi Theja Kambhampati (INTERNATIONAL JOURNAL OF ENGINEERING AND TECHNOLOGY RESEARCH (IJETR), 2024)
This article explores the transformative role of Artificial Intelligence (AI) in education, focusing on its applications in personalized learning and enhanced networking. It examines how AI algorithms analyze student data to create customized learning paths, the implementation of intelligent tutoring systems and adaptive learning platforms, and the use of AI-driven networking to connect students, educators, and experts globally. The article also discusses AI's role in streamlining administrative tasks, the challenges and ethical considerations in AI implementation, and future directions including integration with emerging technologies. The same highlights the potential of AI to create more personalized, engaging, and efficient learning experiences while emphasizing the importance of responsible AI implementation to ensure equitable and ethical use in educational settings.